Hand hygiene knowledge among undergraduate medical students in Junagadh, Gujarat, India - Brahmbhatt, Krutarth R.; Lodhiya, Kaushik K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Hand hygiene is now regarded as one of the most important element of infection control activities. Medical students in their clinical training phase throng the healthcare facilities and can potentially transmit infections besides being the healthcare providers of future when their pattern of training will reflect on their infection control practices. Therefore, this study was carried out to assess the knowledge of undergraduate medical students regarding hand hygiene practices. Methods: A cross-sectional study was carried out and data was collected by using “WHO hand hygiene knowledge questionnaire for health care workers” among 2nd M.B.B.S medical students at Junagadh. Knowledge was graded as good, moderate or poor based on the total number of correct answers. Results: Total 123 students participated in the study. There were 65 (53%) females and 58 (47%) were males. The mean hand hygiene knowledge score (out of 25) was 15.05 (SD: ±2.37, 95% CI: 14.63-15.48). Majority of the participants (76%) had moderate knowledge of hand hygiene practices. Conclusions: In the present study majority of the students had not received formal training regarding hand hygiene practices. Majority of the students had moderate knowledge of hand hygiene. Incorporation of teaching and training of hand hygiene practice in the undergraduate teaching during the initial study years is the need of the hour to prevent further emergence of antimicrobial resistance and health care associated infections.